An Overview of Female Prototypes in "Miragres de Santiago". A First Approach - Fernández Parada, Raquel (Madrygal. Revista de Estudios Gallegos, 2016)
The Miragres de Santiago is one of the most important works in late medieval Galician prose. Dispite of its complex composition, the Christian ideology apparent in this work can be seen as a relevant example of the way of thinking at that time. This essay will try to convey the value of female prototypes by describing, classifying and analysing all references to women. The aim is a first-hand approach to the status of both religious and secular women in the Middle Ages.